Fakul'tetu fizicheskoi kul'tury Kazanskogo gosudarstvennogo pedagogicheskogo universiteta - 50 let - Bobyrev, N. D. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The article is dedicated to the history of physical culture faculty at Kazan State Pedagogical University. The authors analyze the stages of the faculty's development for the last 50 years. They aquaint readers with the famous scientists, managers, teachers, coaches and athletes - whose biography is directly connected with that faculty.